1985
DOI: 10.1099/00221287-131-12-3219
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination by Heat and Proteinase Treatments between Flocculent Phenotypes Conferred on Saccharomyces cerevisiae by the Genes FLO1 and FLO5

Abstract: The effects of elevated temperature and of digestion with a variety of proteinases on the flocforming ability of flocculent strains of Saccharomyces cerevisiae, both genetically defined (FLO1 and FLO5) laboratory and genetically undefined brewing strains, have been determined. This has permitted classification of the flocculent phenotypes of these strains according to criteria other than quantitative grading of flocculence. The flocculent phenotypes conferred by both the FLO1 and the FLO5 gene were irreversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…The rate of flocculation was expressed on a subjective scale ranging from 0 to 4; where 0 indicated the absence of flocculation and 4 indicated extremely flocculent cells. Characterisation of the flocculation phenotype after heat and protease treatment was performed according to Hodgson et al (1985).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of flocculation was expressed on a subjective scale ranging from 0 to 4; where 0 indicated the absence of flocculation and 4 indicated extremely flocculent cells. Characterisation of the flocculation phenotype after heat and protease treatment was performed according to Hodgson et al (1985).…”
Section: Methodsmentioning
confidence: 99%
“…The flocculation of this strain is Ca 2+ , dependent and completely inhibited by EDTA. The properties of the flocculation phenotype of strain 21-45-10 were investigated by heat and protease treatment according to the methods of Hodgson et al (1985). These authors reported that flocculence conferred by the action of the FLO1 gene is easily distinguishable from that determined by the FLO5 gene.…”
Section: Properties Of Wine Yeast Strains 13a and 75bmentioning
confidence: 99%
“…Heat treatment and chymotrypsin treatment of cells were done by the method of Hodgson et a/. 17 ) and the details were described previously. IS) Gentic methods.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that flocculent yeast cells are more resistant to protoplast formation than non-flocculent yeast cells [108]. Recombinant DNA methods have already been used to introduce several new properties into brewing yeasts such as the ability to degrade carbohydrates, modifications to the processes responsible for beer flavour production, and the already referred changes to yeast flocculation [109].…”
Section: Transfer Of Relevant Industrial Properties To Flocculent Yeastmentioning
confidence: 99%